Dysregulation of Alzheimer’s disease-related genes and proteins following cardiac arrest - Ryszard Pluta; Marzena Ułamek-Kozioł; Sławomir Januszewski; Stanisław J. Czuczwar (Folia Neuropathologica, 2017)
Cardiac arrest, usually occurring in the aged population, is the most important cause of high morbidity and death in developed countries. Commonly, attention, depression, cognitive impairment, spatial memory, short- and long-term memory, executive functions, decreased quality of life and social participation are disturbed following circulation arrest. Deficits in cognitive function, similar to prodromal Alzheimer’s disease dementia, following cardiac arrest remain an area of concern. Recent research has focused on the post-resuscitation period to identify mechanisms of long-term brain damage and cognitive impairment. As more patients survive longer periods after cardiac arrest, attention is focused on interventions that may enhance cognitive and psychosocial perceptions. Here, we review the new data influencing the cognitive and functional outcome in the post-resuscitation period.